SONIC LANGUAGE ENRICHMENT: ENHANCING STUDENTS' ENGLISH VOCABULARY THROUGH WESTERN MUSIC - Muhammad Ilham Ali; Frimy Anisa Lestari (PT. Jurnal Center Indonesia Publisher, 2024)
Acquiring vocabulary is a crucial component of English language acquisition for kids. Students require innovative instructional approaches to derive pleasure from the continuous learning process. The teacher should be able to communicate the subject matter and suitably utilize media effectively. This study aimed to ascertain whether the utilization of Music media may yield a noteworthy disparity in enhancing students' English vocabulary and to discover whether the efficacy of music media surpasses that of conventional media. The sample size for this study consisted of 60 students. The system has two classrooms, with each class including a total of 30 students. The pre-test results yielded a t-value of t0 = 1.517, indicating that both classes are worth studying as there is no significant difference in the increase of students' English vocabulary based on the t-test. However, after treatment and the post-test, the t-value obtained was t0 = 3.201, higher than the critical t-value (tt = 2.001) at a significance level of α = 0.05 and degrees of freedom (df) = 58. This indicates a significant difference in students' English vocabulary increase between the experimental class (taught using Music media) and the control class (introduced using conventional press) after the pre-test was administered.